CRIMINAL LAW FUNCTIONALIZATION OF KIDNEY TRAFFICKING FOR TRANSPLANT PURPOSES - Trini Handayani (UNISSULA, 2021)
Kidney transplant is a complete therapy for people with terminal renal failure. The number of cases of terminal renal failure was not proportional to the available donors. Due to the lack of kidney donors, some people take advantage of this opportunity by commercializing their kidneys. In Indonesia's laws and regulations, it is clear that there is a prohibition on the trafficking of organs and or tissues for transplant purposes. Until now, cases of buying and selling of body organs or tissues have never reached the Court. Therefore, it is necessary to formulate a formulation regulating legal protection for all parties concerned. This article aims to analyze the criminal law's functionalization against the trafficking of kidneys for transplant purposes. The research was carried out with a normative juridical approach in a formulated policy structure, namely reviewing and analyzing regulations both in the Criminal Code including the draft criminal law 2005 as an ius constituendum and outside the Criminal Code, specifically regarding the regulation of trade in organs or tissues for transplant purposes. The result of this research is the functionalization of criminal law in the implementation of kidney trade to benefit transplants. Criminal law enforcement is to make criminal law functioned by legally processing the facts of organ trafficking in the field. This repressive action is intended to create a deterrent effect and is a long-term preventive measure so that it is hoped that there will be no more cases of trafficking in organs in the future. It is necessary to understand that the threat of punishment must remain an ultimum remedium, and is enforced if social control is not yet effective.